Development of A Web-Based LMS To Enhance the Effectiveness of Arabic Language Learning at UIN K.H. Abdurrahman Wahid Pekalongan - Ahmad Ubaedi Fathuddin; Muhamad Jaeni; Dicky Anggriawan Nugroho (ALSINATUNA, 2025)
The research objectives were to assess learning effectiveness pre- and post-LMS implementation, identify challenges encountered by users (lecturers and students), and determine specific aspects where the LMS could improve pedagogical outcomes in higher education. A Research and Development (R&D) methodology, structured around the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), was employed. Subjects included students and lecturers from the Arabic Language Education Program. Data collection utilized questionnaires, interviews, and classroom observations, with quantitative data analyzed using ANOVA. Key findings indicated that LMS implementation significantly improved learning outcomes, evidenced by a 15% average increase in student exam scores. Furthermore, 85% of students reported easier access to learning materials, and 78% of lecturers found course and assessment management more streamlined. The novelty of this research lies in the development and empirical validation of an LMS specifically designed for the pedagogical and cultural needs of Arabic language learning in an Indonesian Islamic higher education institution, offering a replicable R&D model. As a recommendation, future development should prioritize mobile optimization and the integration of more diverse interactive features to ensure sustained effectiveness.